Exposure to mine fire related particulate matter and mortality: A time series analysis from the Hazelwood Health Study. (December 2021) - Dimitriadis, Christina; Gao, Caroline X.; Ikin, Jillian F.; Wolfe, Rory; Gabbe, Belinda J.; Sim, Malcolm R.; Abramson, Michael J.; Guo, Yuming
Abstract: Background: In 2014, the Morwell brown coal mine, located in the Latrobe Valley of South eastern Australia, caught fire covering nearby areas in plumes of smoke over a 6-week period. Aims: To investigate the association between exposure to mine fire related air pollution and the risk of mortality. Methods: Time series models were used to evaluate the risk of mortality during the first 30 days of the mine fire, when the smoke was most intense, and in the following six months. Associations were also investigated between mine fire related PM2.5 and mortality. Results: During the 30-day mine fire period, there was an increased risk of death from injury in the most exposed town of Morwell, however no increased risk was observed for all-cause, cardiovascular or respiratory mortality. In the broader Latrobe Valley, males and residents aged 80 and above were at greatest risk of death from injury during the mine fire. In Morwell, during the six months after the mine fire there was an increased risk of all-cause mortality and death from Ischaemic Heart Disease (IHD). Males and residents aged 80 and above in the broader Latrobe Valley, were at increased risk of death from IHD six months after the fire. Conclusions: Coal mine fire exposure was associated with an increase in injury deaths during the mine fire and cardiovascular deaths in the six months after the fire. These findings assist in identifying at risk groups, and improving targeted health advice for future air pollution exposures in the community. Highlights: There was an increase in injury related deaths during the mine fire period. Coal mine fire related PM2.5 was associated with increases in injury related deaths. There was an increase in cardiovascular deaths during the six months after the mine fire period. No increases in respiratory related deaths were observed in relation to exposure to the mine fire.